Accuracy in the diagnosis of vertical root fractures, external root resorptions, and root perforations using cone-beam computed tomography with different voxel sizes of acquisition - Bragatto, Fernanda Paula (J Conserv Dent, 2016)
AIM: The aim of this study is to assess the accuracy of images acquired with cone-beam computed tomography (CBCT) in the identification of three different root alterations. MATERIALS AND METHODS: Forty human premolars were allocated to four experimental groups (n = 10): sound teeth (control), vertical root fracture (VRF), external root resorption (ERR), and root perforation (RP). After the root alterations had been produced, four teeth were randomly assembled into 10 macerated mandibles and submitted to CBCT. Images were acquired with five voxel sizes (0.125, 0.200, 0.250, 0.300, and 0.400 mm) and assessed by three experienced dental radiologists. Sensitivity, specificity, positive and negative predictive values, and the areas under the receiver operating characteristic curve (accuracy) were calculated. The accuracy of imaging in different voxel sizes was compared with Tukey exact binomial test (α=5%). RESULTS: Accuracy with voxel sizes 0.125, 0.200, and 0.250 mm was significantly higher in the detection of ERRs and VRFs than voxel sizes 0.300 and 0.400 mm. No statistical difference was found in terms of accuracy among any of the studied voxel sizes in the identification of RPs. CONCLUSIONS: Voxel size 0.125 mm produced images with the best resolution without increasing radiation levels to the patient when compared to voxel sizes 0.200 and 0.250 mm. Voxel sizes 0.300 and 0.400 mm should be avoided in the identification of root alterations.